Spatial Method to Find Agricultural Fields in Semarang - Wiraguna , Edi; Muliasari , Ade Astri; Situmeang , Widya Hasian; Pratama , Agief Julio; Tandungan , Wempy Sem; Muhaimin , Yahya (Emerging Issues in Environment, Geography and Earth Science Vol. 3, 2023)
This study aims to find suitable agricultural fields to support the growing population in Semarang. GIS (geographic information system), a spatial approach mapping technique, is an appropriate tool for finding a suitable agricultural location. Data resources in GIS software, namely ArcGIS, were accessible information on farmer population, position of roads, rivers, buildings, slopes, and available lands. The information was obtained from the local government. In this project, several stages were taken. First, the number of farmers in each district was compared, and two suitable districts (Mijen and Tugu) were chosen. Second, the length of rivers and the amount of cultivated and uncultivated land in these two selected districts were compared to determine the most suitable district. Finally, the amount of uncultivated land in a selected district (Mijen) was measured and assessed based on distance from a river, road, number of dwellings, structures, and slope. In conclusion, there was an appropriate quantity of potential land in Mijen, Semarang, at around 287.8 hectares. However, there was a need to construct an irrigation system in the district center and a road to the north of Mijen to support water supply and transportation for new designated agricultural areas. The findings indicate that Mijen can produce over 1,500 tonnes of grain corn every growing season in this 287.8 ha of suitable land.